Kettlebell training 95 exercises for strength, toning, stamina, and weight loss - Cotter, Steve 1970- (Human Kinetics, 2014)
Kettlebells can be the ultimate training tool for fat loss, strength, stamina, and coordination. This no-nonsense guide will get you started setting goals, assessing fitness, and selecting exercises utilizing the kettlebells, whether at home or in the gym